Comparison of feeding methods in neonates - A retrospective cohort study from India - Prabha, P C Nayana; Kumar, R Kishore; Shenoi, Arvind (Indian Journal of Child Health, 2017)
Background: Preterm babies who are unable to breastfeed but are able to swallow are commenced on cup or paladai or bottle as alternative feeding methods. Although the World Health Organization recommends the use of cup owing to reduced infection risk, many neonatal units use the bottle for feeding. Objectives: The aim was to compare the two groups with regard to time taken to commence oral feeds, breastfeeds, achieve full oral feeds, complications, gestational age at discharge, discharge weight, and infant formula use at discharge. Material and Methods: This retrospective observational study was performed to compare two cohorts of preterm babies who were fed either by bottle or paladai (small feeding cup with a long spout traditionally used in India) during their transition from tube to breastfeeding. Results: During the study period, there were 68 babies in Center 1 where paladai was used and 71 in Center 2 where bottle was used. The gestational age at which oral feeding was commenced, full oral feeds, gestational age at discharge, and discharge weight were similar in both the groups. Breastfeeding was commenced significantly earlier in the bottle-fed group (p<0.05). The use of infant formula was also significantly more in this group. One baby aspirated in the paladai group. Conclusion: With adequate training and attention to hygiene, paladai or feeding bottles could be equally safe methods of feeding in hospitalized preterm neonates.